PENGADOPSIAN TEKNOLOGI RFID DI RUMAH SAKIT INDONESIA, MANFAAT DAN HAMBATANNYA - Iwan Vanany; Awaluddin Bin Mohamed Shaharoun (Institute of Research and Community Outreach - Petra Christian University, 2009)
This paper explores the benefit and barriers of RFID (Radio Frequency Identification) technology adoption in Indonesian hospitals context. The investigation methods of this research used interview and semi-structured questionnaire on RFID consultants, RFID researchers, and big hospital managers in Java Island. The benefits and barriers of RFID technology adoption are identified from literature review. The barriers of RFID technology adoption are divided into two aspects, i.e., as business and technology aspects. The results of this study suggest that the benefits of RFID technology adoption are dominated of intangible benefit. Most of the respondents believed that the main barriers of RFID technology adoption are (1) the complexity of RFID technology (2) the lack of complete and valid information, and (3) there is no sufficient budget available. The detail of the outcomes and the implications of this reasarch are also discussed. Abstract in Bahasa Indonesia: Makalah ini berupaya mengeksplorasi manfaat dan hambatan dari pengadopsian teknologi RFID (Radio Frequency Identification) dalam konteks rumah sakit di Indonesia. Metode investigasi dari penelitian ini menggunakan wawancara dan kuesioner semi-struktur untuk konsultan, peneliti teknologi RFID dan manajer rumah sakit berkatagori besar di Pulau Jawa. Manfaat-manfaat dan hambatan-hambatan dari pengadopsian teknologi RFID telah diidentifikasi dari studi literatur. Hambatan dari pengadopsian teknologi RFID dibagi menjadi dua (2) aspek yaitu hambatan dari aspek bisnis dan teknologi. Temuan dari studi ini meyakini bahwa manfaat dari pengadopsian teknologi RFID didominasi oleh manfaat yang bersifat intangible. Sebagian besar responden meyakini bahwa hambatan utama dari pengadopsian teknologi RFID adalah: (1) kompleksnya teknologi RFID, (2) ketiadaan informasi yang lengkap dan valid, (3) tidak tersedianya anggaran yang cukup. Detail dari hasil studi dan implikasinya akan didiskusikan selanjutnya. Kata kunci: Pengadopsian teknologi RFID, Rumah sakit, Indonesia, Eksploratori.